2013
DOI: 10.1097/hco.0b013e3283605fba
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat and vascular risk

Abstract: Due to its anatomical and functional proximity to the coronary circulation, epicardial adipose tissue may represent an even more direct CVD risk marker than central adiposity. Lifestyle measures and certain drugs may affect its thickness, although there are limited data currently available. The clinical implications of epicardial fat in daily practice remain to be established in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 88 publications
0
59
1
1
Order By: Relevance
“…It has brown fat characteristics and a role in thermoregulation, modulates coronary vasomotion, and provides a protective framework for cardiac autonomic nerves and ganglia. [10][11][12][13] No fibrous layer exists between EAT and the myocardium or the coronaries, making it possible for free fatty acids, derived from triglyceride breakdown, to directly diffuse into the myocardium or the coronaries and via a paracrine-vasocrine signaling induce atherosclerotic lesion formation in obese individuals. 14 In contrast, EAT could act as a buffer absorbing free fatty acids to prevent cardiac lipotoxicity.…”
Section: Epicardial Adipose Tissue In Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…It has brown fat characteristics and a role in thermoregulation, modulates coronary vasomotion, and provides a protective framework for cardiac autonomic nerves and ganglia. [10][11][12][13] No fibrous layer exists between EAT and the myocardium or the coronaries, making it possible for free fatty acids, derived from triglyceride breakdown, to directly diffuse into the myocardium or the coronaries and via a paracrine-vasocrine signaling induce atherosclerotic lesion formation in obese individuals. 14 In contrast, EAT could act as a buffer absorbing free fatty acids to prevent cardiac lipotoxicity.…”
Section: Epicardial Adipose Tissue In Nafldmentioning
confidence: 99%
“…10 The most interesting hypothesis is that EAT can function as an endocrine organ that contributes to the inflammatory burden. 7,[9][10][11][12][13] The expression of the anti-inflammatory adiponectin is lower in EAT. 26 Several small studies have reported correlations between EAT and metabolic risk factors.…”
Section: Epicardial Adipose Tissue In Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Epicardial adipose tissue functions as an active endocrine organ that produces several cytokines involved in oxidative stress, atherosclerosis, inflammation and angiogenesis [2]. Various studies have highlighted the potential importance of adipose tissue in relation to inflammatory burden in cardiovascular diseases.…”
mentioning
confidence: 99%
“…CT remains the modality of choice for diagnosing the necrotic changes in the epipericardial and pericardial fat tissue ( 3,4 ). Magnetic resonance imaging may be utilized for diagnosis ( 5 ), but is typically unnecessary. Features of epipericardial fat necrosis include a self-limiting course and typical resolution of fi ndings on repeat imaging ( 6,7 ).…”
Section: Discussionmentioning
confidence: 99%